2017
DOI: 10.1021/acs.biochem.7b00509
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Regulation of Pantothenate Biosynthesis by the PanD–PanZ·AcCoA Complex Reveals an Additional Mode of Action for the Antimetabolite N-Pentyl Pantothenamide (N5-Pan)

Abstract: The antimetabolite pentyl pantothenamide has broad spectrum antibiotic activity but exhibits enhanced activity against Escherichia coli. The PanDZ complex has been proposed to regulate the pantothenate biosynthetic pathway in E. coli by limiting the supply of β-alanine in response to coenzyme A concentration. We show that formation of such a complex between activated aspartate decarboxylase (PanD) and PanZ leads to sequestration of the pyruvoyl cofactor as a ketone hydrate and demonstrate that both PanZ overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…This may not only affect CoA biosynthesis but the resulting metabolites are also inferred to inhibit downstream CoA‐utilizing pathways, leading to lethal effects on P . falciparum , as suggested for bacteria . Based on their synthetic accessibility, high potency and low cytotoxicity, pantothenamides would be excellent candidates for antimalarial drug development .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may not only affect CoA biosynthesis but the resulting metabolites are also inferred to inhibit downstream CoA‐utilizing pathways, leading to lethal effects on P . falciparum , as suggested for bacteria . Based on their synthetic accessibility, high potency and low cytotoxicity, pantothenamides would be excellent candidates for antimalarial drug development .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] This may not only affect CoA biosynthesis but the resulting metabolites are also inferred to inhibit downstream CoA-utilizing pathways, leading to lethal effects on P. falciparum, [9,10] as suggested for bacteria. [12][13][14][15][16][17][18][19][20] Based on their synthetic accessibility,h igh potency and low cytotoxicity,pantothenamides would be excellent candidatesf or antimalarial drug development. [21] Unfortunately, however,p antetheinases (also knowna sv anins) in human serum rapidlyh ydrolyzep antothenamides into pantothenate and the corresponding amine (Figure 1b), [8,22] making them unsuitable for therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…For E.coli , which has a PanK I type enzyme, the presumed mechanism of action of the pantothenamide N5-pan has been investigated in detail. The formation of coenzyme A antimetabolites [9] that interferes with fatty acid synthetic enzymes [11] and endogenous pantothenate biosynthesis [28] are two affected pathways that are interrupted. It was also reported that N5-Pan could inhibit the growth of S. pneumoniae and that this effect was probably due to fatty acid synthesis inhibition as it could be outcompeted with oleate [10].…”
Section: Discussionmentioning
confidence: 99%
“…To further complicate matters, not all pantothenamides known to yield crypto-ACP species are toxic to E. coli [95], implying again that other factors may be involved in the antibacterial activity of pantothenamides. Recent studies looking at the mode of action of 1 in E. coli suggest that its resulting CoA antimetabolite ( 14) may also affect aspartate decarboxylation by PanD (within the pantothenate biosynthetic pathway) by binding to its regulatory protein PanZ [122]. AcCoA is known to bind to the PanD-PanZ complex and inhibit the production of pantothenate; this effect may be reproduced by metabolite 14 which binds to PanZ with equal affinity as AcCoA [122][123].…”
Section: Mechanism Of Action Of Pantothenamides In E Colimentioning
confidence: 99%